Identification of Dynamic Models of Vertical Motion for a Multi-rotor Flying Platform - Michał DUDA (Identyfikacja modeli dynamicznych ruchu pionowego dla wielowirnikowej platformy latającej, 2024)
The article presents the results of identifying dynamic models for an unmanned multi-rotor platform. Due to such an object’s highly complex mathematical model, it was decided to identify dynamic models based on experimental data. The identification concerns vertical movement parameters, but also energy consumption when performing maneuvers, which is a key factor for autonomous aircraft.
Keywords: Wielowirnikowa platforma latająca